PEMBANGKIT GRUP PERSAMAAN SCHRODINGER - Aloysius Joakim Fernandez (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2018)
In this article contains the Group’s concepts in mathematical analysis namely self-adjoint property and Stone Theorem. This theorem talks about generator infinitesimal of Group. Moreover, this article will discuss the concepts of Group in Schrodinger equation.